2005
DOI: 10.1242/jcs.02281
|View full text |Cite
|
Sign up to set email alerts
|

Myofilin, a protein in the thick filaments of insect muscle

Abstract: Thick filaments in striated muscle are myosin polymers with a length and diameter that depend on the fibre type. In invertebrates, the length of the thick filaments varies widely in different muscles and additional proteins control filament assembly. Thick filaments in asynchronous insect flight muscle have an extremely regular structure, which is likely to be essential for the oscillatory contraction of these muscles. The factors controlling the assembly of thick filaments in insect flight muscle are not know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
39
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 37 publications
(44 reference statements)
7
39
0
Order By: Relevance
“…Note however that a visible gap remains in the M-line region, suggesting that flightin is excluded from the bare zone. This agrees with immuno-EM studies of the flightin homologue (zeelin-2) in the IFMs of the water bug Lethocerus indicus, where the protein was shown to be absent from the bare zone (Ferguson et al, 1994;Reedy et al, 2000;Qiu et al, 2005). These authors also showed that flightin was absent from the very tips of the thick filaments of the A/I junction, presumably due to the presence of the connecting filaments (consisting of sallimus and projectin) in that region (Ferguson et al, 1994), though this is not resolvable in our work due to limitations of confocal microscopy.…”
Section: Discussionsupporting
confidence: 85%
“…Note however that a visible gap remains in the M-line region, suggesting that flightin is excluded from the bare zone. This agrees with immuno-EM studies of the flightin homologue (zeelin-2) in the IFMs of the water bug Lethocerus indicus, where the protein was shown to be absent from the bare zone (Ferguson et al, 1994;Reedy et al, 2000;Qiu et al, 2005). These authors also showed that flightin was absent from the very tips of the thick filaments of the A/I junction, presumably due to the presence of the connecting filaments (consisting of sallimus and projectin) in that region (Ferguson et al, 1994), though this is not resolvable in our work due to limitations of confocal microscopy.…”
Section: Discussionsupporting
confidence: 85%
“…Flightin binds the light meromyosin region of myosin, ϳ2/3 of the way down the rod, because substituting aspartic acid 1554 for lysine abolishes flightin's interaction in vitro (1) and accumulation in vivo (18). Immunolocalization studies in Drosophila and Lethocerus IFM indicate that flightin is associated with the thick filament backbone (25,26), consistent with studies that show flightin is absent in IFM lacking thick filaments (29).Studies using Drosophila mutants demonstrate that flightin plays several important roles in maintaining muscle integrity. Flightin is required for normal thick filament assembly and for establishing or maintaining in vivo filament length and flexural rigidity (8,26).…”
supporting
confidence: 79%
“…Flightin binds the light meromyosin region of myosin, ϳ2/3 of the way down the rod, because substituting aspartic acid 1554 for lysine abolishes flightin's interaction in vitro (1) and accumulation in vivo (18). Immunolocalization studies in Drosophila and Lethocerus IFM indicate that flightin is associated with the thick filament backbone (25,26), consistent with studies that show flightin is absent in IFM lacking thick filaments (29).…”
supporting
confidence: 79%
“…The expressed gene set also included two isoforms of myofilin, a 20‐kDa protein associated with myosin in the core of thick filaments that make up asynchronous insect flight muscle (Qiu et al . 2005). The transcription of genes coding for proteins associated with locomotory muscles (e.g.…”
Section: Resultsmentioning
confidence: 99%